Differences in preventing new‐onset cardiovascular events with statin therapy in seniors aged 75 years and over: A cohort study in the South Korean National Health Insurance Database. Issue 2 (15th April 2019) - Kim, Kyungim; Kwak, Arim; Choi, Cheol Ung; Kim, Jae Hyun; Kim, Myeong Gyu; Oh, Jung Mi; Ji, Eunhee
Abstract: The aim of this cohort study was to compare the effectiveness of statin regimens for primary prevention among seniors aged ≥ 75 years. Seniors aged 75‐100 years for whom statin therapies for primary prevention were newly initiated between 1 January 2009 and 31 December 2011, and who continued the same statin regimen during the first year after the index date were identified using the claims data from the South Korean National Health Insurance Database. A propensity score matching and multivariable Cox proportional hazards model were developed to evaluate adjusted ischaemic cardiovascular‐cerebrovascular event (CCE) risk and all‐cause mortality risk for all patients, as well as for subgroups. A total of 5629 older patients aged 75‐100 years were included in the study population. Compared to moderate‐intensity statin therapy, low‐intensity statin therapy was significantly associated with increased risk of ischaemic CCEs, while high‐intensity statin therapy was associated with reduced risk of ischaemic CCEs; however, compared to moderate‐intensity statin therapy, both low‐intensity and high‐intensity statin therapies were associated with increased risk of all‐cause mortality. For the 4689 older patients who regularly received moderate‐intensity statin therapy including 10 mg atorvastatin, 20 mg atorvastatin, 10 mg rosuvastatin or 20 mg simvastatin for primary prevention, multivariable regression adjusting for potential covariates revealed no significant difference in ischaemic CCEs or all‐cause mortality between the moderate‐intensity statin users and 10 mg atorvastatin users both before and after propensity scoring matching. No significant heterogeneity was detected in the patient subgroups. The results of this study based on real‐world data can supply evidence‐based reasons for choice of statin regimen for the primary prevention of CCEs in older people aged ≥ 75 years.